Impact of molar-incisor hypomineralization on oral health-related quality of life in Vietnamese schoolchildren - Le, Van Nhat Thang; Nguyen , Thi Thuy Uyen; Chau, Ngoc Phuong Thanh; Lee, Dae-Woo (Tạp chí Y Dược Huế, 2025)
Background: Although molar-incisor hypomineralization (MIH) is prevalent in Asian countries, no studies have evaluated its impact on oral health-related quality of life (OHRQoL). The aim of this study was to determine the impact of MIH on OHRQoL in Vietnamese schoolchildren. Materials and methods: This cross-sectional study with 432 Vietnamese children aged 8-10 years was conducted in Hue city, Vietnam. OHRQoL was measured using the Child Perceptions Questionnaire for 8- to 10-year-olds (CPQ 8 - 10). The presence and severity of MIH was evaluated using the European Academy of Pediatric Dentistry (EAPD) criteria. A non-parametric Kruskal-Wallis test was applied for multiple intergroup comparisons, followed by Dunn’s test. A p-value <0.05 was the threshold for statistical significance. Statistical analysis was performed using SPSS version 26.0 and GraphPad Prism software version 9.0.0. Results: Children with MIH had significantly higher CPQ 8 - 10 median scores than those without MIH, indicating that MIH negatively impacts OHRQoL. Similar trends were observed across all four domains: oral symptoms [3 (1 - 4) vs. 4 (3 - 7)]; functional limitations [1 (0 - 2) vs. 3 (1 - 6)]; emotional well-being [2 (0 - 4) vs. 4 (1 - 7)]; and social well-being [1 (0 - 3) vs. 2 (1 - 7)]. Regarding severity, CPQ 8 - 10 overall scores increased from mild [12 (7 - 19)] to severe [30 (23 - 33)] forms of MIH. Conclusion: MIH was associated with impaired OHRQoL. With increasing severity, this condition showed a more significant negative impact on OHRQoL. To confirm these findings, further studies should be performed with the Parental-Caregivers Perceptions Questionnaire.